Challenges Faced by Cut Flowers Growers in Tamil Nadu.(with Special Reference to Nilgiris District) - Vasanthi, S. (Indian Journal of Marketing, 2008)
Flowers are one of the nature’s most beautiful gifts to man. Their beauty and fragrance brings joy and happiness to our lives. In any garden, flowers in great variety are always the main attraction. Their colour combination, fragrance, and the skill with which they have been grown and displayed count a lot. Since time immemorial, flowers have been considered as the symbol of grace and elegance and a feast for our eyes. They are used on all religious and festive occasions. Flowers are used as birthday presents, wedding gifts, or while meeting ailing people and even at funerals. Most Hindu ladies adorn their hair style with flowers. "Veni", a special kind of hair decoration with flowers has been widely used in South India to decorate the long plaits of hair during dance recitals and at wedding ceremonies. All people irrespective of their ethnic origin, race, sex and cadre love flowers. It is for this reason that the Society of America Florists has adopted a slogan "say it with flowers".